Hematopoietic Stem Cell Transplantation: A Bioethical Lens. (27th June 2017) - Liso, Arcangelo; Neri, Margherita; Maglietta, Francesca; La Russa, Raffaele; Turillazzi, Emanuela
Abstract : Hematopoietic stem cell transplantation (HSCT) is one of a range of therapeutic options available to patients suffering from various diseases. HSCT procedure involves important ethical and legal aspects that can occur at every phase of the procedure: the clinical choice of whether to perform the procedure, pretransplantation preparation regimens, donor selection, stem cell harvest procedure, transplantation phase, and short-term and long-term follow-up care. In this discussion paper, we outline the ethical issue-facing physicians involved in HSCT. Currently, HSCT is a widely accepted treatment for many life-threatening diseases. It thus represents a real therapeutic hope for many patients. It does, however, carry a burden of possible morbidity and mortality. Consequently, there are substantial information and communication issues involved in the consent process for HSCT. In the final decision, the judgements of different parties, such as patients, family members, and healthcare professionals, intersect and overlap and this is particularly true when the patient is a minor. Finally, HSCT is a very expensive procedure. The social and economic concerns of HSCT are discussed within the actual contextual framework of the dramatic increase in healthcare costs and inequalities in healthcare in relation to socioeconomic status, educational status, and ethnicity.